The Implementation Green Building at Syamsudin Noor Airport - Ahmad Busairi; Tambun, Madschen SMOSS; Agustina Hotma Uli Tumanggor (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
The development of Syamsudin Noor Airport is expected to have a major impact on the economy of the people of South Kalimantan. However, the construction of airports will have an impact on the environment due to the increasing number of human activities. And to anticipate these adverse effects, Syamsudin Noor Airport applies the concept of Green Building. The purpose of this study is to provide a descriptive picture of the extent to which Syamsudin Noor Airport has implemented the concept of green building. From the observations, Syamsudin Noor Airport has implemented green buildings such as solar panels, the use of bright glass that allows natural light to enter the terminal space, wastewater treatment facilities, green open spaces in the airport terminal area, bicycle parking and shower compartments, room temperature settings that create comfort in working, and the presence of no-smoking signs. With the implementation of green buildings at Syamsudin Noor Airport to meet the service standards set in the Presidential Law of the Republic of Indonesia No. 1 of 2009, supporting an environmentally friendly workplace and reducing operational costs.